CCN Family 2/Connective Tissue Growth Factor Modulates BMP Signalling as a Signal Conductor, Which Action Regulates the Proliferation and Differentiation of Chondrocytes - Maeda, Azusa (2008)
Both CCN family 2/connective tissue growth factor (CCN2/CTGF) and bone morphogenetic protein (BMP)-2 play an important role in cartilage metabolism. We evaluated whether or not CCN2 would interact with BMP-2, and examined the combination effect of CCN2 with BMP-2 (CCN2-BMP-2) on the proliferation and differentiation of chondrocytes. Immunoprecipitation-western blotting analysis, solid-phase binding assay and surface plasmon resonance (SPR) spectroscopy showed that CCN2 directly interacted with BMP-2 with a dissociation constant of 0.77 nM as evaluated by SPR. An in vivo study revealed that CCN2 was co-localized with BMP-2 at the pre-hypertrophic region in the E18.5 mouse growth plate. Interestingly, CCN2-BMP-2 did not affect the BMP-2/CCN2-induced phosphorylation of p38 MAPK but caused less phosphorylation of ERK1/2 in cultured chondrocytes. Consistent with these results, cell proliferation assay showed that CCN2-BMP-2 stimulated cell growth to a lesser degree than by either CCN2 or BMP-2 alone, whereas the expression of chondrocyte marker genes and proteoglycan synthesis, representing the mature chondrocytic phenotype, was increased collaboratively by CCN2-BMP-2 treatment in cultured chondrocytes. These findings suggest that CCN2 may regulate the proliferating and differentiation of chondrocytes by forming a complex with BMP-2 as a novel modulator of BMP signalling.